Evaluation of musculoskeletal symptoms and of work ability in a higher education institution - Denise Hollanda Iunes; Melissa Louyse Duarte; Leticia do Vale Pereira; Murilo César do Nascimento; Valdeci Carlos Dionisio
Introduction Work-related musculoskeletal disorders (WMSDs) represent a significant object of study for the field of occupational health, as they can lead to absenteeism, compensation costs and different levels of functional disability. Nonetheless, there are few studies assessing WMSDs in public higher education institutions. Objective The present study aimed to investigate, describe and correlate musculoskeletal symptoms and work ability of staff members of the Federal University of Alfenas (Unifal-MG), in the state of Minas Gerais, Brazil. Materials and methods A descriptive and correlational study was conducted with 213 professors, 188 administrative technicians and 124 outsourced staff members using two self-administered questionnaires: the Work Ability Index (WAI) and the Nordic Musculoskeletal Questionnaire (NMQ). Results Most of the teaching staff presented good work ability 47.9% (n = 102). Among administrative technicians and outsourced staff, on the other hand, excellent work ability predominated, with 43.6% (n = 82 technicians) and 51.61% (n = 68 outsourced). The most affected region among professors and administrative staff was the neck/cervical area 36.15% (n = 77 professors); and 28.19% (n = 53 technicians). Among outsourced staff, the lower back was reported as the main source of pain, with 23.28% (n = 29). Conclusions The presence of pain interfered in the work ability of workers regardless of the affected region. Having another occupation outside the institution did not influence pain of self-assessed staff members. The work ability of Unifal-MG staff was classified as good or excellent; thus, we recommend preventive work for this population, directed at the physical and mental aspects of work activities in order to maintain or improve such rates.